Toddlers’ Judgments of Media Character Source Credibility on Touchscreens. - Richards, Melissa N.; Calvert, Sandra L. (American Behavioral Scientist, 2015)
In three experiments, 32-month-old children (n = 40 for Experiment 1, n = 36 for Experiment 2) and 24-month-old children (n = 33 for Experiment 3) were asked to judge the credibility of information presented on a touchscreen device. The information was delivered by a familiar and an unfamiliar media character. Two app conditions varied on which character was accurate in naming familiar fruits. Then both characters labeled four novel fruits with nonsense words. Feedback about the accuracy of the characters’ labels of the familiar fruits was provided in Experiments 1 and 3, but no such feedback was provided in Experiment 2. Children were more likely to endorse the accurate character as the correct labeler of the novel fruits, regardless of prior familiarity with the character, the feedback presented in the touchscreen application, or the age of the child. Parent scaffolding affected only the 24-month-old children. The results reveal that very young children can make relatively sophisticated judgments about the credibility of information encountered on touchscreen devices.